Sequence Diversity, Locus Structure, and Evolutionary History of the SpTransformer Genes in the Sea Urchin Genome - Barela Hudgell, Megan A.; Smith, L. Courtney (Frontiers in Immunology, 2021)
The generation of large immune gene families is often driven by evolutionary pressure exerted on host genomes by their pathogens, which has been described as the immunological arms race. The SpTransformer (SpTrf) gene family from the California purple sea urchin, Strongylocentrotus purpuratus, is upregulated upon immune challenge and encodes the SpTrf proteins that interact with pathogens during an immune response. Native SpTrf proteins bind both bacteria and yeast, and augment phagocytosis of a marine Vibrio, while a recombinant SpTrf protein (rSpTrf-E1) binds a subset of pathogens and a range of pathogen associated molecular patterns. In the sequenced sea urchin genome, there are four SpTrf gene clusters for a total of 17 genes. Here, we report an in-depth analysis of these genes to understand the sequence complexities of this family, its genomic structure, and to derive a putative evolutionary history for the formation of the gene clusters. We report a detailed characterization of gene structure including the intron type and UTRs with conserved transcriptional start sites, the start codon and multiple stop codons, and locations of poly-adenylation signals. Phylogenetic and percent mismatch analyses of the genes and the intergenic regions allowed us to predict the last common ancestral SpTrf gene and a theoretical evolutionary history of the gene family. The appearance of the gene clusters from the theoretical ancestral gene may have been driven by multiple duplication and deletion events of regions containing SpTrf genes. Ectopic duplications and insertion events, indels and point mutations in the exons likely resulted in the extant genes and family structure. This theoretical evolutionary history is consistent with the involvement of these genes in the arms race in responses to pathogens and suggests that the diversification of these genes and their encoded proteins have been selected for based on the survival benefits of pathogen binding and host protection.